A comprehensive morphometric analysis of superior and inferior mesenteric arteries using cadaveric dissection and MDCT angiography - Sneha Guruprasad Kalthur; Rajagopal Kadavigere; Vrinda Hari Ankolekar; Dhiren Punja; Rohini Punja (Translational Research in Anatomy, 2024)
Background: Superior mesenteric artery (SMA) and inferior mesenteric artery (IMA) are vital vascular structures supplying the majority of the intestinal tract. Despite their clinical significance, comprehensive morphometric studies combining traditional cadaveric dissection with modern imaging techniques are scarce in literature. This study aimed to provide a detailed morphometric analysis of the SMA and IMA using both cadaveric dissection and multi-detector computed tomography (MDCT) angiography. Methods: The study utilized a dual approach, combining cadaveric dissection (30 formalin-fixed cadavers) and MDCT angiography (images from 50 patients). Measurements including stem lengths, diameters at origin, and distances from the aortic bifurcation were taken, along with assessment of vertebral levels of origin and branching patterns. Data from both components were analyzed using descriptive statistics. Results: Key findings for SMA include: Mean stem length: 3.19 ± 0.72 cm (cadaveric) vs. 2.53 ± 0.53 cm (MDCT); Mean diameter at origin: 0.93 ± 0.22 cm (cadaveric) vs. 0.57 ± 0.10 cm (MDCT); Most common vertebral level of origin: Upper border of L1 (78 % of cases); Branching pattern variations observed in 23.3 % of cadaveric specimens, which included the origin of the inferior pancreaticoduodenal artery from the first jejunal artery, a common trunk for right colic and ileocolic arteries, and absence of middle colic artery. For IMA: Mean stem length: 3.61 ± 1.29 cm (cadaveric) vs. 3.41 ± 0.69 cm (MDCT); Mean diameter at origin: 0.50 ± 0.11 cm (cadaveric) vs. 0.26 ± 0.05 cm (MDCT); Most common vertebral level of origin: Upper border of L3 (40 % of cases). No variations observed in branching pattern. Conclusions: The detailed measurements, frequency of variations, and comparison between traditional and modern assessment techniques offer a nuanced understanding of mesenteric vascular anatomy. This study bridges the gap between classical anatomical knowledge and contemporary imaging capabilities, potentially improving surgical planning, interventional procedures, and radiological interpretation.